1988
DOI: 10.1126/science.3388032
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral Dissociation of Dishabituation, Sensitization, and Inhibition in Aplysia

Abstract: Three forms of nonassociative learning (habituation, dishabituation, and sensitization) have commonly been explained by a dual-process view in which a single decrementing process produces habituation and a single facilitatory process produces both dishabituation and sensitization. A key prediction of this view is that dishabituation and sensitization should always occur together. However, we show that dishabituation and sensitization, as well as an additional process, inhibition, can be behaviorally dissociate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

24
159
0

Year Published

1993
1993
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 191 publications
(183 citation statements)
references
References 18 publications
24
159
0
Order By: Relevance
“…Both sensitization and dishabituation (Characteristic 4) may involve the introduction of a stimulus from another modality. Results are conventionally described as "dishabituation" if the added stimulus restores responsiveness to an already habituated stimulus and as "sensitization" if the added stimulus increases responding before substantial habituation occurs to the other stimulus (e.g., Marcus, Nolen, Rankin, & Carew, 1988 Groves and Thompson (1970) argued that a companion process, sensitization, often, but not always, accompanies that of habituation.…”
Section: Changes In Reinforcer Effectiveness Produce Within-session Cmentioning
confidence: 99%
“…Both sensitization and dishabituation (Characteristic 4) may involve the introduction of a stimulus from another modality. Results are conventionally described as "dishabituation" if the added stimulus restores responsiveness to an already habituated stimulus and as "sensitization" if the added stimulus increases responding before substantial habituation occurs to the other stimulus (e.g., Marcus, Nolen, Rankin, & Carew, 1988 Groves and Thompson (1970) argued that a companion process, sensitization, often, but not always, accompanies that of habituation.…”
Section: Changes In Reinforcer Effectiveness Produce Within-session Cmentioning
confidence: 99%
“…The reduction in the response can last from minutes to hours depending on the type of stimulus and study conducted. This type of response, often referred to as non-associative learning, has been shown by a variety of organisms from the invertebrates Aplysia, Tritonia, and Drosophila, to rats, using different types of stimuli (Marcus et al, 1988;Pletnikov et al, 1995;Brown, 1998;Cho et al, 2004). One of the prominent behaviors studied in vertebrates is the startle response, a fast contraction of body muscles caused by a sudden acoustic, tactile, or visual stimulus mediated by simple neuronal circuitry (Koch, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…Inhibitory interactions within the ganglion play an important role in regulating the strength of the withdrawal reflex (Marcus et al, 1988;Small et al, 1989Small et al, , 1992Wright et al, 1991;Trudeau and Castellucci, 1992;Fischer and Carew, 1993). For example, recently Fischer and Carew (1993) found that an inhibitory feedback loop plays an important role in regulating the total synaptic input to the LFS motorneurons, and Trudeau and Castellucci (in press) found that cholinergic inhibition similarly influences the input to the motorneurons.…”
Section: Variability In Response Of Lfs Neurons To Fmrfamidementioning
confidence: 99%
“…5-HT's facilitatory effects on the presynaptic sensory neurons include a decrease in spike threshold, spike broadening, and an increase in transmitter release (Brunelli et al, 1976;Castellucci and Kandel, 1976;Klein and Kandel, 1980;Walters et al, 1983;Klein et al, 1986;Dale and Kandel, 1990). Recently, it has been found that inhibitory inputs also have important modulatory effects on the magnitude of the withdrawal reflex (Mackey et al, 1987;Marcus et al, 1988;Krontiris et al, 1989;Wright et al, 1991;Small et al, 1992;Trudeau and Castellucci, 1992;Fischer and Carew, 1993) and at least one mechanism of behavioral inhibition involves presynaptic modulation of transmitter release from the siphon sensory neurons (Mackey et al, 1987).…”
mentioning
confidence: 99%